2008
DOI: 10.1007/s12253-008-9109-x
|View full text |Cite
|
Sign up to set email alerts
|

Serum sFas and Tumor Tissue FasL Negatively Correlated with Survival in Egyptian Patients Suffering from Breast Ductal Carcinoma

Abstract: Fas (CD95-APO-1), a member of tumor necrosis factor receptor super-family, exists in two forms, transmembrane and soluble (sFas). It had been suggested that circulating sFas levels and/or tissue FasL may reflect the severity of invasive breast ductal carcinoma. Few studies showed that neither DNA-index nor ploidy is an independent prognostic indicator, and there is no correlation with clinical outcome. The S-phase fraction (SPF) has been shown to be useful prognostic factor in both node-negative and node-posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Increased FasL levels have been detected in various cancer types including breast and pancreatic cancer (El-Sarha et al ., 2009; Mullauer et al ., 2000; Muschen et al ., 1999; Ohta et al ., 2004; Pernick et al ., 2002). This can provide the proliferative signal for circulating MSCs and/or MSCs in the TME.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased FasL levels have been detected in various cancer types including breast and pancreatic cancer (El-Sarha et al ., 2009; Mullauer et al ., 2000; Muschen et al ., 1999; Ohta et al ., 2004; Pernick et al ., 2002). This can provide the proliferative signal for circulating MSCs and/or MSCs in the TME.…”
Section: Resultsmentioning
confidence: 99%
“…Several reports have described this as Fas-threshold signalling, in which low concentrations of FasL resulted in survival signalling and growth (Bentele et al , 2004; Lavrik et al , 2007; Paulsen et al , 2011). In clinical samples, FasL has been found at elevated levels in various cancer types (Belt et al , 2014; Botti et al , 2004; El-Sarha et al , 2009; Herrnring et al , 2000; Mottolese et al , 2005; Mullauer et al , 2000; Muschen et al , 1999; Ohta et al , 2004; Pernick et al , 2002; Sjostrom et al , 2002; Song et al , 2001; Zhang et al , 2005), and has been associated with tumour progression (Barnhart et al , 2004; Chen et al , 2010; Hoogwater et al , 2010; Kleber et al , 2008; Lin et al , 2012; Malleter et al , 2013; Peter et al , 2015; Teodorczyk et al , 2015; Trauzold et al , 2005; Zhang et al , 2009; Zheng et al , 2013). Most of this work, however, focused on Fas/FasL signalling in cancer cells without consideration of the more complex cellular interactions and regulatory circuits between malignant and non-malignant cells, such as MSCs, present in the TME (Shi et al , 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Our results are consistent with shown that FasL expression is frequently upregulated in breast cancer. [18] Further El-Sarha AI et al, [19] observed that FasL expression directly correlated with distant metastasis and poor overall survival.…”
Section: Discussionmentioning
confidence: 97%
“…Increased FasL expression has been detected in various cancer types, including breast and pancreatic cancer [17,[20][21][22][23]. This can provide the proliferative signal for circulating MSCs and/or MSCs in the TME.…”
Section: Fasl Induces Proliferation In Mscs Via Mapk/erkmentioning
confidence: 99%
“…Several reports have described this as Fasthreshold signalling, in which low concentrations of FasL promote survival signalling and growth [11][12][13][14]. In patient samples, FasL has been found at elevated levels in various cancer types [15][16][17][18][19][20][21][22][23][24][25][26], and has been associated with tumour progression [27][28][29][30][31][32][33][34][35][36][37]. Most of this work, however, has focused on Fas/FasL signalling in cancer cells without consideration of the more complex cellular interactions and regulatory circuits between malignant and non-malignant cells, such as MSCs, present in the TME [38].…”
Section: Introductionmentioning
confidence: 99%